2008
DOI: 10.1110/ps.036319.108
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic barriers and the role of topology in protein and RNA folding

Abstract: This review compares the folding behavior of proteins and RNAs. Topics covered include the role of topology in the determination of folding rates, major folding events including collapse, properties of denatured states, pathway heterogeneity, and the influence of the mode of initiation on the folding pathway.Keywords: protein structure/folding; RNA folding Proteins and RNAs must fold into specific structures in order to carry out their functions within the cell. For both biomolecules, the stability and specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 123 publications
(143 reference statements)
2
35
1
Order By: Relevance
“…32,50 Secondly, many TSEs contain a high fraction of the native structure and topology (e.g., the TSE has $70% of the native state's relative contact order). [20][21][22]32,51 This high level eliminates many otherwise possible transition state structures, and further reduces the amount of heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…32,50 Secondly, many TSEs contain a high fraction of the native structure and topology (e.g., the TSE has $70% of the native state's relative contact order). [20][21][22]32,51 This high level eliminates many otherwise possible transition state structures, and further reduces the amount of heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, folding rates are independent of topological complexity for fast folding molecules (Sosnick and Pan 2004). From the limited information comparing folding of a few RNA classes, it is generally believed that a correlation between folding rate and topology depends upon whether the ratelimiting step involves disruption of non-native interactions or small local conformational changes that act as nucleation scaffolds (Treiber and Williamson 2001a;Sosnick 2008).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Of the studies that monitored intracellular RNA structure formation, only few have attempted a comprehensive correlation of in vitro versus in vivo folding paradigms. 6,12 As the folding pathway of the ai5γ ribozyme has been thoroughly studied in vitro at non-physiological conditions, 1 we aimed at elucidating how this large, multidomain RNA, which depends on the helicase Mss116p for efficient splicing in vivo, folds in yeast.…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise site of action of Mss116p during the early folding steps remains enigmatic both in vitro and in vivo. In any case folding of the scaffolding domain appears to be a critical step at non-physiological conditions, 21 near-physiological conditions with 3 and without Mss116p 19 as well as in yeast mitochondria. Aside from accelerating the Mg 2+ -induced collapse of ai5γ in an ATP-independent manner, it has been shown that ATP hydrolysis is necessary for the protein's turnover and that Mss116p does not stabilize the native state of the ribozyme, but that such stabilization results from binding of flanking exons.…”
Section: Notementioning
confidence: 99%
See 1 more Smart Citation